Determinación de la prefactibilidad de obtención de isobutano y propano, usando gases de extracción petrolífera en Colombia (2018)
In this research project, the determination of the pre-factibility of obtaining isobutane and propane, from Natural Gas and LPG was carried out, based on the need for the elimination of synthetic refrigerants by natural refrigerants, which contribute to the reduction of emissions of gases that damage the ozone layer and global warming, therefore to verify that in Colombia this type of gases can be obtained, for this reason a simulation was carried out in Aspen Hysys, to corroborate that if isobutane and propane can be obtained 99.5% in purity.